2021
DOI: 10.3389/fcimb.2020.586354
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine Upregulates Entamoeba histolytica Virulence Factors, Enhancing Parasite Pathogenicity in Experimental Liver Amebiasis

Abstract: Entamoeba histolytica is an invasive enteric protozoan, whose infections are associated to high morbidity and mortality rates. However, only less than 10% of infected patients develop invasive amebiasis. The ability of E. histolytica to adapt to the intestinal microenvironment could be determinant in triggering pathogenic behavior. Indeed, during chronic inflammation, the vagus nerve limits the immune response through the anti-inflammatory reflex, which includes acetylcholine (ACh) as one of the predominant ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 70 publications
(64 reference statements)
1
8
0
Order By: Relevance
“…The relative expression of genes coding for the intermediate and heavy subunit of the Gal/GalNAc lectin (150 and 170 kDa) ( Table 1 ) important participants in amoebic pathogenesis was evaluated; expression levels were normalized to the α-tubulin gene. It has been reported that the relative expression of these subunits increases after interaction with exogenous ACh ( Medina-Rosales et al., 2021 ). Furthermore, trophozoites inhibited at the Gal/GalNAc lectin binding sites with N-acetylgalactosamine and interacted with ACh did not express the 170 kDa and 150 kDa genes compared to the control; instead, trophozoites interacted directly with ACh did show an increased relative expression of the Gal/GalNAc lectin genes (150 and 170 kDa) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative expression of genes coding for the intermediate and heavy subunit of the Gal/GalNAc lectin (150 and 170 kDa) ( Table 1 ) important participants in amoebic pathogenesis was evaluated; expression levels were normalized to the α-tubulin gene. It has been reported that the relative expression of these subunits increases after interaction with exogenous ACh ( Medina-Rosales et al., 2021 ). Furthermore, trophozoites inhibited at the Gal/GalNAc lectin binding sites with N-acetylgalactosamine and interacted with ACh did not express the 170 kDa and 150 kDa genes compared to the control; instead, trophozoites interacted directly with ACh did show an increased relative expression of the Gal/GalNAc lectin genes (150 and 170 kDa) ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore the presence of ACh at the site of infection can affect the elimination of the parasite from the body. In a previous study, our research group determined that the interaction between ACh and E. histolytica causes an increase in its virulence factors such as adhesion, synthesis, and secretion of amebapore C, and cysteine proteinase 2 ( ehcp-a2 ) and cysteine proteinase 5 ( ehcp-a5 ) and a significant increase in amebic liver abscess in hamsters ( Medina-Rosales et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. histolytica is an anaerobic parasitic invasive enteric protozoan, and infections of E. histolytica correlate to high mortality and morbidity rates[ 11 , 12 ]. Each year, this protozoan causes 40000-100000 deaths, ranking only behind malaria in patient mortality[ 13 - 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each year, this protozoan causes 40000-100000 deaths, ranking only behind malaria in patient mortality[ 13 - 15 ]. According to a previous report, invasive amebiasis develops in fewer than one-tenth of patient infections[ 11 ]. The geographic distribution of amebiasis has worldwide amplitude and a high rate of incidence, and it remains a public health concern in low- and middle-income developing countries in the tropics, particularly in environments that are crowded and lacking in adequate sanitation and clean water due to the oral-fecal route of pathogen transmission (including ingestion of food or water that contains cysts from this protozoan)[ 6 , 16 - 19 ].…”
Section: Introductionmentioning
confidence: 99%